Synthesis, crystal structure and Hirshfeld surface analysis of 5,5-diphenyl-2-[2-(propan-2-ylidene)hydrazin-1-yl]-4,5-dihydro-1H-imidazol-4-one N,N-dimethylformamide hemisolvate - Abderrazzak El Moutaouakil Ala Allah; Benson M. Kariuki; Walid Guerrab; Abdulsalam Alsubari; Musa A. Said; Joel T. Mague; Youssef Ramli (Acta Crystallographica Section E: Crystallographic Communications)
The asymmetric unit of the title structure, 2C18H18N4O2·C3H7NO, consists of two independent molecules of the substituted imidazolone having different conformations, and one molecule of solvent DMF. The two imidazolone molecules are linked by N—H...N and C—H...O hydrogen bonds and the DMF is joined to one of these by an N—H...O hydrogen bond. Additional N—H...N and C—H...O hydrogen bonds link these groups into corrugated layers parallel to the (101) plane with the layers joined by C—H...π (ring) interactions. A Hirshfeld surface analysis indicated that H...H interactions account for over half of the intermolecular contacts.